Effect of Ni doping on the properties of Ca(OH)2 nanoparticles and its application in toxic methylene blue dye removal - Akash; Pushpendra Kumar; Vipin Kumar; Ashok Kumar Sharma; Anoop Kumar Mukhopadhyay (Results in Physics)
This work reports the successful synthesis of calcium hydroxide nanoparticles (CHNPs) and doped it with various concentrations (3–12 atom%) of Ni, using a simple co-precipitation method. The CHNPs and nickel-doped calcium hydroxide nanoparticles (Ni-CHNPs) samples were examined for their structural, elemental, functional group, surface morphology, thermal, and optical analysis using various characterization techniques. Structural analysis confirmed that Ni ions were effectively incorporated into the Ca(OH)2 lattice without disrupting its crystalline integrity. The Ni doping in CHNPs is further confirmed by XPS and EDX spectra. The crystallite size and optical band gap of Ni-CHNPs were found to vary with a change in the doping concentration of Ni. Further, the effect of Ni doping was observed in surface morphology and thermogravimetric data. The changes in the properties of Ni-CHNPs with varying concentrations of Ni were discussed in terms of the interaction between Ni and CHNPs. The synthesized material was then used to study the adsorption capacity (qe) and percentage removal (%R) of dyes from wastewater. Furthermore, the effect of temperature on the adsorption characteristics of methylene blue (MB) dye by the Ni-CHNPs is marked by a consistent increase in (%R) and (qe) as the temperature rises from 25 °C to 45 °C. Among these, the sample with 9 at.% Ni showed the highest adsorption efficiency at 45 °C, achieving ∼ 90 % dye removal. The adsorption kinetics of dye were analyzed using several kinetics models, out of which the adsorption of MB was best described by the pseudo-second order (PSO) model. These results provide valuable insights into the properties of Ni-CHNPs and their potential applications in dye removal for further development in environmental remediation technologies.